Serum 25-Hydroxyvitamin D Level is Associated with Arterial Stiffness, Left Ventricle Hypertrophy, and Inflammation in Newly Diagnosed Hypertension. (August 2013) - Kuloğlu, Osman; Gür, Mustafa; Şeker, Taner; Kalkan, Gülhan Yüksel; Şahin, Durmuş Yıldıray; Tanboğa, İbrahim Halil; Koyunsever, Nermin Yıldız; Harbalıoğlu, Hazar; Türkoğlu, Caner; Akyol, Selahattin; Elbasan, Zafer; Acele, Armağan; et al.
Objectives: Vitamin D may modulate vascular inflammation, vascular smooth muscle cell proliferation, the renin-angiotensin system, and cardiomyocyte proliferation, myocardial fibrosis, and proliferation. These mechanisms may play a role on arterial stiffness and left ventricle hypertrophy (LVH) in hypertensive patients. We aimed to evaluate the association between serum vitamin D with arterial stiffness and LVH in patients with hypertension. Methods: We studied 133 patients with newly diagnosed hypertension [mean (SD) age, 62.9 (10.6) years]. Pulse wave velocity (PWV), which reflects arterial stiffness, was calculated using the single-point method via the Mobil-O-Graph ARCsolver algorithm. Left ventricular mass index (LVMI) was determined according to Deverux formula. The patients were divided into the following 2 groups according to serum vitamin D level: vitamin Dlow group with less than 20 ng/mL and vitamin Dhigh group with greater than or equal to 20 ng/mL. Results: The highest PWV, high-sensitivity C reactive protein, and LVMI values were observed in vitamin Dlow group compared with vitamin Dhigh group. Multiple linear regression analysis showed that vitamin D level was independently associated with LVMI (β = −0.235, P = 0.002) and PWV (β = −0.432, P < 0.001). Adjustment for age, sex, parathyroid hormone level, body surface area, and mean blood pressure did not modify these associations. Vitamin D level was also independently associated with high-sensitivity C reactive protein (β = −0.143, P = 0.047). However, adjustment for parathyroid hormone level or body surface area and mean blood pressure attenuate this association. Conclusions: Serum 25-hyroxyvitamin D is independently related with arterial stiffness, LVH, and inflammation. Vitamin D may play a role on pathogenesis of arterial stiffness and LVH in patient with newly diagnosed hypertension.